Experimental studies on in-cylinder combustion, exergy performance, and exhaust emission in a Compression Ignition engine fuelled with neat biodiesels - Aditya Kolakoti; Ambati Vijay Kumar; Raghu Metta; Muji Setiyo; Muhammad Latifur Rochman (Indonesian Journal of Science and Technology, 2022)
In the last decade, the search for cleaner fuels like biodiesels is gaining wide popularity, and exergy analysis are widely used in design and performance evaluation to identify the various losses. In this study, three neat biodiesels are tested for energy and exergetic performance in a single-cylinder, four-stroke IDI diesel engine. The experiments are conducted for waste poultry fat biodiesel (WPFBD), palm oil biodiesel (POBD), and waste cooking oil biodiesel (WCOBD) at various loads by maintaining a fixed rpm of 1500. Parameters like exergetic efficiency, exergy destruction, and various heat loss factors are computed from the thermodynamic models. The in-cylinder combustion pressures, heat release rate, and fuel consumption are also measured. Results show that WCOBD dominates the other two biodiesels by achieving high exergetic efficiency (52.74%) and low exergetic destruction (3.74 kJ). The in-cylinder combustion pressures and net heat release for WCOBD show smoother combustion with better torque conversion. In contrast, POBD shows high fuel consumption and more unaccounted heat losses. Better utilization of heat input by converting it into useful work was achieved for WCOBD at 75 and 100% loads. Similarly, the exhaust emissions from WCOBD compared with diesel fuel at all the loads reveal that except for NOx, there is a drastic reduction of CO, UHC, and exhaust smoke.